2015
DOI: 10.1021/acs.orglett.5b01363
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole-Based Boron Dipyrromethenes (BODIPYs): Facile Synthesis, Structures, and Fine-Tunable Optical Properties

Abstract: Carbazole-based BODIPYs were synthesized in three steps using an organometallic approach consisting of sequential Ir-catalyzed borylation, Suzuki-Miyaura coupling, and boron complexation. Various substituents were introduced into the carbazole moiety, and large substituent effects were confirmed by means of absorption spectroscopy, cyclic voltammetry, and DFT calculations. Dibenzocarbazoles were also converted into the corresponding BODIPYs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…Forexample,the reaction of 10 b bearing methoxy and mesyloxy groups (as R 1 and R 2 ,r espectively) with 11 d delivered the annulation products with relatively low regioselectivity (12/13 75:25;e ntry 5), although we did observe an increase in the combined yield to 83 %. After several failed attempts at the borylation [21] or lithiation [22] of the C5 position, we successfully introduced am ethoxy group through ad ibromination- [e] When the catalyst loading was decreased to 2mol %, slightly lower yields were observed (47 %yield for 12 cd;58% yield for 12 dd). We subsequently decided to use the annulation product 12 dd (entry 7) for the total synthesis of dictyodendrins,onthe basis of the efficacyofthe annulation reaction as well as the facile removal of the tert-butyl group.T hus,t he reaction was conducted on ag ram scale (10 d:2 .76 g; 11 d:6 .69 g) with ad ecreased amount of the catalyst (162 mg, 2mol %), and product 12 dd (2.27 g) was isolated in 58 %y ield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Forexample,the reaction of 10 b bearing methoxy and mesyloxy groups (as R 1 and R 2 ,r espectively) with 11 d delivered the annulation products with relatively low regioselectivity (12/13 75:25;e ntry 5), although we did observe an increase in the combined yield to 83 %. After several failed attempts at the borylation [21] or lithiation [22] of the C5 position, we successfully introduced am ethoxy group through ad ibromination- [e] When the catalyst loading was decreased to 2mol %, slightly lower yields were observed (47 %yield for 12 cd;58% yield for 12 dd). We subsequently decided to use the annulation product 12 dd (entry 7) for the total synthesis of dictyodendrins,onthe basis of the efficacyofthe annulation reaction as well as the facile removal of the tert-butyl group.T hus,t he reaction was conducted on ag ram scale (10 d:2 .76 g; 11 d:6 .69 g) with ad ecreased amount of the catalyst (162 mg, 2mol %), and product 12 dd (2.27 g) was isolated in 58 %y ield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Maeda et al . have shown the incorporation of carbazole units to porphyrinoids and BODIPY frameworks generated interesting photophysical properties . A recent report on four‐coordinate organoboron complexes derived from indole‐azaheteroaryl ligands showed wide range of emission from blue to orange .…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Maeda et al have shown the incorporation of carbazole units to porphyrinoids and BODIPY frameworks generated interesting photophysical properties. [25][26][27] A recent report on four-coordinate organoboron complexes derived from indole-azaheteroaryl ligands showed wide range of emission from blue to orange. 28 However, small Stokes shifts (<15 nm) are one of the main drawbacks for the application of BODIPY dyes in molecular imaging due to the self-absorption effect resulting in less intensive emission.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] We have previously investigated the synthesis and photophysicalp rop-erties of carbazole-based porphyrinoids and recentlyr eported the facile synthesiso fc arbazole-based BODIPYs (Scheme 1). [8] Various substituents could be introduced onto the carbazole moiety and efficient substituent effects were confirmed. However,t hese carbazole-based BODIPYd yes showede xtensive fluorescenceq uenchingd ue to intramolecular charge transfer (ICT).…”
Section: Introductionmentioning
confidence: 99%